Septic hip dislocations in children in a developing country - Gabriel Ngom; Olivier Ngaringuem; Desiré Allumeti Munyali; Mbaye Fall; Oumar Ndour; Mamadou Ndoye (Wolters Kluwer Medknow Publications, 2011)
Purpose: To report on a radiological issue and therapeutic aspects encountered in septic hip dislocations in a developing country. Patients and Methods: Nineteen children among whom 11 boys and 8 girls aged on average 5.3-years old presented 7 recent and 12 late hip dislocations. Those dislocations were distributed into in category 1: dislocations without associated lesion; category 2: dislocations associated with minor lesions; category 3: dislocations associated with major lesion. Ten children who presented an elevated erythrocyte sedimentation rate (ESR) received antibiotics. An arthrotomy was performed in children with a recent dislocation. Traction was performed in all children with an average duration of 5 weeks. The results were considered good, intermediate or bad using two parameters: ESR and reduction of dislocation. Results: 2 category 1 dislocations, 6 category 2 dislocations and 11 category 3 dislocations were noted. As concerns the recent dislocations, there were 2 category 1 dislocations and 5 category 2 dislocations. For late dislocations, 1 category 2 and 11 category 3 dislocations were recorded. There were 8 good results and 11 bad results. The good results concerned 7 recent dislocations and one late dislocation. The bad results concerned exclusively late dislocations. Conclusion: In children with septic hip dislocations, the good results concern almost exclusively recent dislocations but arthrotomy and immobilization must be done early.